2003
DOI: 10.1002/arch.10073
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ecdysone agonists on vitellogenesis and the expression of EcR and USP in codling moth (Cydia pomonella)

Abstract: The effects of tebufenozide and methoxyfenozide on vitellogenin (Vg) synthesis/release in the fat body, translocation in hemolymph, uptake by the ovary, and the expression of the ecdysone receptor (EcR) and its heterodimer partner, ultraspiracle protein (USP) in fat body, were investigated in Cydia pomonella. The results indicated that both ecdysone agonists significantly increased the Vg level in the adult hemolymph when the moths were exposed to agonist-treated surfaces. However, these agonists did not affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 43 publications
4
16
0
Order By: Relevance
“…Although ecdysteroids were not measured in this study, it is reasonable to hypothesize that the effects that we observed on the fecundity of S. exigua also could be due to changes in ecdysteroid concentrations caused by methoxyfenozide in the eggs of this insect. If so, then vitellogenesis and embryogenesis were altered, as has previously been reported in C. pomonella (Sun et al 2003). This hypothesis is supported by a study carried out by Berghiche et al (2008) in which halofenozide was observed to increase the amounts of both free ecdysteroids and 20E in T. molitor eggs.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Although ecdysteroids were not measured in this study, it is reasonable to hypothesize that the effects that we observed on the fecundity of S. exigua also could be due to changes in ecdysteroid concentrations caused by methoxyfenozide in the eggs of this insect. If so, then vitellogenesis and embryogenesis were altered, as has previously been reported in C. pomonella (Sun et al 2003). This hypothesis is supported by a study carried out by Berghiche et al (2008) in which halofenozide was observed to increase the amounts of both free ecdysteroids and 20E in T. molitor eggs.…”
Section: Discussionsupporting
confidence: 64%
“…This effect could explain the reduction in reproductive parameters reported previously in studies using ecdysone agonists in several insect pests (Farinó s et al 1999;Knight 2000;Sun et al 2000Sun et al , 2003Taibi et al 2003;Saenz-de-Cabezon et al 2005;Pineda et al 2006;Osorio et al 2008,). Future studies should clarify where and how methoxyfenozide acts to cause the observed changes in the concentrations of carbohydrates, proteins, and lipids.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Seth et al (2004) have reported the deposition of RH-5992 in the gonads of both male and female S. littoralis leading to sterility. Reduction in fecundity and fertility in codling moth Cydia pomonella (L., 1758) was also reported by Sun et al (2000Sun et al ( , 2003.…”
Section: Discussionsupporting
confidence: 54%
“…An earlier survey of the toxic effects of RH 5849 on different orders of insects indicated that one species of dipterans (Neobellieria bullata) was affected deleteriously (Darvas et al 1992). In addition to disrupting development of insect larvae, the compounds also affected diapause and reproduction of treated insects (Gadenne et al, 1990;Swevers and Iatrou, 1999;Sun et al, 2003;Seth et al, 2004). Moreover, treatment with the compound RH 5849 triggered yolk polypeptide synthesis (which is normally characteristic of females) in several species of male flies including Drosophila and Phormia (DeLoof et al, 1997).…”
Section: Archives Of Insect Biochemistry and Physiologymentioning
confidence: 95%